2011
DOI: 10.1016/s0377-5291(12)70010-x
|View full text |Cite
|
Sign up to set email alerts
|

A Rational Approach to Dental Management of Patients on Bisphosphonates

Abstract: There has been a lot of focus on osteonecrosis of the jaws associated with the usage of bisphosphonates both in dental and medical literature in recent years. However, the exact pathogenesis of bisphosphonate-related osteonecrosis of the jaws remains unclear. Against the background of emerging evidence of an evolving condition, it is not surprising that there is a lack of robust evidence-based recommendations on dental treatment of patients on bisphosphonates. This paper seeks to provide a rational approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…This is a reliable index for evaluating the bone turnover rate and the anti-resorptive therapy. [43] Whether the serum CTX value is as a good index to predict the risk of BRONJ is controversial. Marx et al, [44] found lower serum CTX values in patients with BRONJ.…”
Section: Serum Collagen Telopeptidementioning
confidence: 99%
“…This is a reliable index for evaluating the bone turnover rate and the anti-resorptive therapy. [43] Whether the serum CTX value is as a good index to predict the risk of BRONJ is controversial. Marx et al, [44] found lower serum CTX values in patients with BRONJ.…”
Section: Serum Collagen Telopeptidementioning
confidence: 99%